PBAF Subunit Pbrm1 Selectively Influences the Transition from Progenitors to Pre-Myelinating Cells during Oligodendrocyte Development - Waldhauser, Vanessa; Baroti, Tina; Fröb, Franziska; Wegner, Michael (Cells, 2023)
Oligodendrocyte development is accompanied by defined changes in the state of chromatin that are brought about by chromatin remodeling complexes. Many such remodeling complexes exist, but only a few have been studied for their impact on oligodendrocytes as the myelin-forming cells of the central nervous system. To define the role of the PBAF remodeling complex, we focused on Pbrm1 as an essential subunit of the PBAF complex and specifically deleted it in the oligodendrocyte lineage at different times of development in the mouse. Deletion in late oligodendrocyte progenitor cells did not lead to substantial changes in the ensuing differentiation and myelination processes. However, when Pbrm1 loss had already occurred in oligodendrocyte progenitor cells shortly after their specification, fewer cells entered the pre-myelinating state. The reduction in pre-myelinating cells later translated into a comparable reduction in myelinating oligodendrocytes. We conclude that Pbrm1 and, by inference, the activity of the PBAF complex is specifically required at the transition from oligodendrocyte progenitor to pre-myelinating oligodendrocyte and ensures the generation of normal numbers of myelinating oligodendrocytes.
CRIS-Team Scopus Importer:2023-07-28
Keywords: chromatin remodeling; glia; myelin; oligodendrocyte; polybromo-1

Role of the Pbrm1 subunit and the PBAF complex in Schwann cell development - Polanetzki, Vanessa; Fröb, Franziska; Baroti, Tina; Schimmel, Margit; Tamm, Ernst R.; Wegner, Michael (Scientific Reports, 2022)
Myelin sheath formation in the peripheral nervous system and the ensuing saltatory conduction rely on differentiated Schwann cells. We have previously shown that transition of Schwann cells from an immature into a differentiated state requires Brg1 that serves as the central energy generating subunit in two related SWI/SNF-type chromatin remodelers, the BAF and the PBAF complex. Here we used conditional deletion of Pbrm1 to selectively interfere with the PBAF complex in Schwann cells. Despite efficient loss of Pbrm1 early during lineage progression, we failed to detect any substantial alterations in the number, proliferation or survival of immature Schwann cells as well as in their rate and timing of terminal differentiation. As a consequence, postnatal myelin formation in peripheral nerves appeared normal. There were no inflammatory alterations in the nerve or other signs of a peripheral neuropathy. We conclude from our study that Pbrm1 and very likely the PBAF complex are dispensable for proper Schwann cell development and that Schwann cell defects previously observed upon Brg1 deletion are mostly attributable to altered or absent function of the BAF complex.
CRIS-Team Scopus Importer:2022-02-25